2017
DOI: 10.1039/c7pp00115k
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of quinones by thiols sensitized by phthalocyanines

Abstract: Under the irradiation of red light (690 nm), quinones were converted to hydroquinones by thiols in the presence of metallophthalocyanines. The reaction proceeded via the charge separation between the triplet state of phthalocyanine and the quinone. The product determining step was protonation of the quinone anion radical, as indicated by the fact that the reaction was accelerated by the use of more acidic thiols or addition of an acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Quinone chemistry has been extensively investigated, including nucleophilic addition and cycloaddition reactions, photochemistry and oxidative coupling. [38][39][40][41][42][43][44][45] The versatility of quinonoidal compounds has stimulated chemists to attempt a variety of synthetic transformations. In the last few years, considerable efforts have been devoted to the functionalization of quinones, including alkylation, arylation, amination, and sulfenylation via 1,4addition.…”
Section: Introductionmentioning
confidence: 99%
“…Quinone chemistry has been extensively investigated, including nucleophilic addition and cycloaddition reactions, photochemistry and oxidative coupling. [38][39][40][41][42][43][44][45] The versatility of quinonoidal compounds has stimulated chemists to attempt a variety of synthetic transformations. In the last few years, considerable efforts have been devoted to the functionalization of quinones, including alkylation, arylation, amination, and sulfenylation via 1,4addition.…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced electron transfer (PET) reaction is one of the key processes in solar energy conversion reactions both in natural and artificial systems. Of particular interest is the development of a PET reaction driven by near-infrared (NIR) light (>700 nm), which accounts for more than 40% of the solar energy reaching on the earth, because of potential applications of the reaction, such as dye-sensitized solar cells , and artificial photosynthesis, , in addition to its fundamental importance. , In this context, extensive efforts have been devoted to construct PET systems using NIR absorbing compounds including Ru and Rh complexes, phthalocyanines, BODIPYs, , and some organic radicals. , However, most of these studies have demonstrated the PET systems driven by visible light (≤700 nm) and there are only a few reports on NIR light-induced electron transfer (NIR-ET) systems. Furthermore, all of the reports on NIR-ET systems are limited to static quenching systems, in which a photosensitizer (PS) and a quencher (Q) must be assembled at their ground states. The development of NIR-ET systems based on dynamic quenching, in which PS and Q do not have to associate with each other at the ground state and thus a systematic investigation with various combinations of PS and Q is allowed, must broaden the diversity of PET systems and lay the foundation for the research field.…”
Section: Introductionmentioning
confidence: 99%